Kemampuan Representasi Matematis Siswa dalam Memecahkan Masalah Relasi dan Fungsi Kelas VIII SMP - Iffa, Dini Sofiatul; Subarinah, Sri; Baidowi, Baidowi; Sripatmi, Sripatmi (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2022)
This study aimed to knowing and describe students' mathematical representation skills in solving relational and function problems for class VIII in academic year 2021/2022. The research method used was descriptive research with a qualitative approach. The instruments used were mathematical representation ability tests and interview. The research subjects were students VIII C with 30 students who were given a mathematical representation ability test grouped into high, medium, and low categories based on their mathematical ability. From each category, 2 students were selected to be interviewed further. In general, from the test results, students with high mathematical representation abilities have been able to achieve indicators of mathematical representation abilities with an achievement percentage of 82.63% which is very good. Students with moderate mathematical representation skills with an achievement percentage of 51.26%, which is sufficient. and students with low mathematical representation skills with an achievement percentage of 25.95%, which is less. From the results of interviews, students with high mathematical mathematical representation abilities were able to explain the answers to the test results very well. Students with moderate mathematical representation skills are quite able to explain their answers well. Students with low mathematical representation ability are able to explain the answer but the explanation given is less detailed.